Advanced design of the pasta drying process with simulation tools. (1st January 2013) - Armenzoni, Mattia; Solari, Federico; Marchini, Davide; Montanari, Roberto; Bottani, Eleonora; Vignali, Giuseppe; Ferretti, Gino
This work aims at investigating the industrial drying process of pasta. The analysis carried out consists of two parts. First, a scientific method, called finite difference model (FDM), was applied to the drying process of pasta, with the purpose of developing a simulation model able to reproduce the process. The model was implemented under Microsoft Excel TM, through an ad hoc spreadsheet that automatically calculates the trend of temperature and moisture as a function of time for a simple cylindrical product of infinite length (i.e., spaghetti). The results obtained from the Microsoft Excel TM simulator were then validated by means of: 1) the comparison with a real industrial case; 2) the comparison with the results provided by computational fluid dynamics (CFD) software, called 'TdynMultiphysics' (for the thermal results). In the second part, we analysed the industrial equipment used for the drying process, i.e., the static dryer. A CFD model was developed with the commercial software Tdyn Multiphysics, with the purpose of assessing the performance of four different layouts of a static dryer for pasta. The ultimate aim is to investigate the performance of the drying process as a function of the dryer configuration in order to optimise it.